Macroeconomic Economic factors affecting the sale volumes of auto leasing of H Company Limited - ปิยะโสภาสกุล, ชนะชล; เจริญวิริยะกุล, ศิริขวัญ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
This research aims to study the Macroeconomic Economic factors affecting the sale volumes of auto leasing of H Company Limited. The factors examined in this study include Thailand's Gross Domestic Product (GDP), the Monetary Policy Committee’s interest rate, inflation rate, global oil prices, government policies promoting the automotive industry, and the COVID-19 situation. The study utilizes secondary time-series data on a quarterly basis from 2014 to 2023, covering a total of 40 quarters. A multiple regression analysis was conducted using the least squares method. The study found that the effect on the sales of auto hire purchase loans of H company limited consist of Thailand’s Gross Domestic Product (GDP) and government policies promoting the automotive industry significantly explains the relationship at a 0.01 significance level in the same direction. Meanwhile, the Monetary Policy Committee’s interest rate, inflation rate, global oil prices, and the COVID-19 situation were found to be statistically insignificant.